Al-Aşīl Wa al-Dakhīl: Sumber Autentik dan Non-Autentik Penafsiran Al-Qur’an - Eka Sulistiyawati; Anni Anisa (Penerbit Hellow Pustaka, 2024)
In Islamic tradition, the interpretation of the Qur’an is one of the most important disciplines. The exegete or expert in exegesis has the task of explaining the meaning of the verses of the Qur’an, so that they can be understood and practiced by Muslims in various aspects of life. To carry out this task, the exegete uses various sources that are considered authoritative in interpreting the Qur’an. However, the sources used by the exegete are often the object of discussion and debate, especially in terms of their validity and authority. Thus, the issue of the sources used by the exegete is not unly a technical problem in interpretation, but also concerns the issue of authority, methodology, and the relevance of religious teachings in the context of changing times. Apart from this background, this study aims to explain the sources used by interpreters, both authentic and non-authentic sources. This study uses a type of library research and a qualitative approach. The results of the study, the author concludes that the authentic sources of interpretation that can be used in interpreting the Qur’an are; Qur’an, hadith, the words of the companions, the words of the tābi‘īn, Arabic, and ijtihad. While non-authentic sources include; hadith maudhū’ and isrāilliyāt.